QUALITY OF SERVICE, SAFETY AND TRUST IN CONSUMER SATISFACTION AT THE SAP DELIVERY SERVICE (SATRIA ANTARAN PRIMA) AMBON BRANCH - Erlinda Tehuayo; Victor E. Huwae; Abdul Ajis Difinubun (Jurnal Ekonomi, 2023)
This study aims to determine the effect of service quality, security and trust on customer satisfaction at the SAP delivery service (Satria Anteran Prima) Ambon Branch. This research is a quantitative descriptive research. The population in this study are consumers on SAP services (satria and prima) and the number of samples is 106 respondents. By using a questionnaire as a data collection tool. Sampling using non probability sampling technique with purposive sampling method. The data analysis method used is Multiple Linear Regression. Based on the results of the multiple regression test, it shows that the service quality variable has a positive and significant influence on customer satisfaction. Furthermore, the security variable has a positive and significant effect on consumer satisfaction and the trust variable has a positive and significant effect on customer satisfaction.